Supportive parenting and adolescents digital citizenship behaviors: The mediating role of self-regulation - Agustín Morales-Álvarez; Angel Alberto Valdés-Cuervo; Lizeth Guadalupe Parra-Pérez (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
A plethora of studies have shown that parenting practices can lead to problematic Internet use. However, few studies have explored how parents foster positive online behavior in adolescents. This study addresses this gap by using self-determination theory to examine how supportive parenting practices, such as autonomy support and structure provision, can influence digital citizenship behaviors in adolescents. The study considered the mediating role of adolescents’ self-regulation, and examined how sex and adolescence stage moderate these relationships. The study included 570 Mexican adolescents (48% girls and 52% boys), and structural equation modeling and multigroup invariance statistics were conducted for analysis. The results showed that autonomy support was positively associated with all dimensions of digital citizenship, while structure provision was only positively associated with online civic engagement. Self-regulation was found to mediate the relationship between autonomy support, structure provision, and digital citizenship behaviors. The multigroup analysis confirmed that sex and adolescence stage did not affect the relationship between parenting practices and digital citizenship behaviors. Overall, the results suggest that supportive parenting practices can encourage positive digital citizenship behaviors among adolescents.